A Fast, Sensitive and Accurate High Resolution Melting (HRM) Technology-Based Assay to Screen for Common K-ras Mutations - D. Kramer; F. B. Thunnissen; M. I. Gallegos-Ruiz; E. F. Smit; P. E. Postmus; C. J. L. M. Meijer; P.J.F. Snijders; D. A. M. Heideman (Cellular Oncology)
Background: Increasing evidence points to a negative correlation between K-ras mutations and patient’s response to, or survival benefit after, treatment with EGFR-inhibitors. Therefore, rapid and reliable assays for mutational analysis of the K-ras gene are strongly needed.